Bone health in children with severe cerebral palsy - Barbier, Vincent; Goeb, Vincent; Gouron, Richard; Fritot, Severine; Mentaverri, Romuald; Klein, Céline (Frontiers in Pediatrics, 2023)
Aim To describe bone health and associated factors in children with severe cerebral palsy. Method In a retrospective, single-centre study, we performed a comprehensive bone evaluation (including clinical, densitometric and bone biomarker assessments) of children with severe cerebral palsy. Results None of the 19 included children had a normal BMCTBLH Z score, and only one had a BMDTBLH Z score greater than −2. Six children had a BMDLS Z score greater than −2. The bone biomarker data were suggestive of excessive bone remodelling. Levels of bone remodelling markers factors and densitometric variables were not significantly related. Age, weight and pubertal stage were significantly related to bone mass. Discussion Our results highlights the insufficient increase in bone mass with age (probably due to excessive bone remodelling) and confirms the high prevalence of low bone mineral density in children with severe cerebral palsy. Possible preventive measures might include calcium + vitamin D supplementation and the systematic management of underweight and delayed puberty. Bone remodelling markers might be of value for follow-up.